Reimplante dentário após a obturação do canal com pasta de β-glicerofosfato de cálcio ou pasta de hidróxido de cálcio: estudo histomorfométrico em ratos - Damante, Simone Carrijo [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Tooth avulsion occurs mainly young patients who have teeth with incomplete root formation. In this case the pulp necrosis is common and apexification is impaired. The large foramen hinders insertion of dressings and delay final obturation of root canal. Therefore it is important to use a bandage to facilitate the formation of mineralized tissue barrier permitting the apical seal. Calcium hydroxide has been the most used material for this purpose. However require a long period of changes. In the literature was described that calcium β- glycerophosphate has the ability to induce formation of mineralized tissue in a shorter period of time. This possibility justifies this study to analyze histologically the action of this material as intracanal dressing in delayed tooth replantation. In this study 40 male rats were divided into 4 groups of 10 animals. In Group I, the teeth were extracted and replanted immediately into their alveoli source. In the other groups, extracted teeth were kept dry for 60 minutes. The dental papilla, enamel organ and pulp tissue were removed. The periodontal ligament was also removed and the teeth were immersed in a phosphate acidulated sodium fluoride solution, for 10 minutes. In Group II, the root canals were filled with saline. Group III used the calcium hydroxide paste and Group IV used the calcium β-glycerophosphate paste. The teeth were reimplanted and euthanasia was performed 60 days later for histology analysis with HE. The results showed that the groups II and IV were more compromised by inflammatory root resorption than groups I and III. Group I had less involvement by total reabsorption than group II (p <0,05). In all groups the periapical region was occupied by a fibrous connective tissue with inflammatory infiltrate. It is concluded that β-glycerophosphate calcium was not more effective than calcium hydroxide in the control of root resorption and repair of the periapical area of mineralized tissue

A avulsão dentária acomete principalmente pacientes jovens e que possuem dentes com rizogênese incompleta. Nesse caso a necrose pulpar é frequente e a apicificação é prejudicada. O amplo forame dificulta a inserção de curativos de demora e a obturação definitiva do canal. Assim é importante o uso de um curativo de demora para favorecer o controle da reabsorção radicular e a formação de uma barreira de tecido mineralizado permitindo o selamento apical. O hidróxido de cálcio tem sido o material mais utilizado para esse fim, necessitando, porém, de um longo período de trocas. Existem relatos na literatura de que o β-glicerofosfato de cálcio também possui a capacidade de induzir a formação de tecido mineralizado em um período mais curto de tempo. Essa possibilidade justificou a realização deste estudo para analisar histologicamente a ação deste material como curativo de demora em reimplante tardio de dentes ratos. Foram empregados 40 ratos machos divididos em 4 grupos de 10 animais. No Grupo I os dentes foram extraídos e reimplantados imediatamente em seus alvéolos de origem. Nos demais grupos, os dentes extraídos foram mantidos em meio seco por 60 minutos. A papila dentária, o órgão do esmalte e a polpa foram removidos. O ligamento periodontal também foi removido e os dentes foram imersos em solução de fluoreto de sódio fosfato acidulado por 10 minutos. No Grupo II os canais radiculares foram preenchidos com soro fisiológico. No Grupo III, utilizou-se a pasta de hidróxido de cálcio e no Grupo IV utilizou-se a pasta de β-glicerofosfato de cálcio. Os dentes foram reimplantados e a eutanásia dos animais foi realizada 60 dias depois para processamento histológico em H.E. Os resultados demonstraram que os grupos II e IV foram mais comprometidos pela reabsorção...
Keywords: Reimplante dentário; Avulsão dentária; Hidróxido de cálcio; Reabsorção da raiz; Dente não vital; Obturação do canal radicular; Tooth replantation